ANALISIS NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUKU CERITA ANAK HEBAT SEBAGAI ALTERNATIF BAHAN AJAR PAI DI KELAS IV SEKOLAH DASAR - SIPAULAILIAH, - (2023)
Storybooks are one of the tools that can be used to gain knowledge and can entertain. Story books are made according to the characteristics of children so that they are easy to understand and contain character values in them. Character values need to be instilled early on in children, because in addition to having good cognitive abilities and skills, children must also have good character and personality. At this time, the selection of story books for children needs to be done so that the messages received by children can grow character values. The components supporting the process of teaching and learning are teaching materials, because teaching materials have a very important role in the provision of character values. This study uses a qualitative method approach to content analysis. The research instrument in this study was the researcher himself, the data analysis techniques used were data collection, data reduction, data presentation, drawing conclusions/verification. Based on the results of the analysis, it was found that there were 50 data findings which contained 14 character values, namely character values (1) religious, (2) honest, (3) discipline, (4) hard work, (5) creative, (6) independent, (7) curiosity, (8) love of the motherland, (9) respect for achievement, (10) friendly/communicative, (11) peace-loving, (12) fond of reading, (13) social care, and (14) responsibility answer. Then from the results of the analysis, the researcher made the results of the analysis an alternative lesson material for Islamic Religious Education for grade IV Elementary School. Keywords: Story Books, Character Values, Teaching Materials